PENINGKATAN MENULIS SURAT MELAUI MEDIA SMART BOX DI SMA SWASTA NURUL ILMI PADANGSIDEMPUAN TAHUN PELAJARAN 2024-2025 - Adawiyah, Robiyatul; Gultom, Fita Delia; Caniago, Elnila (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This research was conducted through Smart Box media to see the improvement of students' letter writing skills at SMA Negeri Nurul Ilmi Padangsidempuan. The number of samples in this study was 34 students out of 134 students with an average value of 50.06 in the pre-action, there were still many students who had not completed the KKM, a percentage of 38.23% who had not reached the KKM. While with the treatment through cycle I there were 18 students with a percentage of 52.94%. with an average value of 70.22. This has not reached the target, so the action was carried out again through cycle II, namely the Improvement of 80% who have reached the target so that the hypothesis is accepted.